Evaluación de un Modelo de Asistencia de Puntos de Referencia en Dispositivos Móviles para Personas Ciegas - Chaves-Alvarado, Alexander (Instituto Tecnológico de Costa Rica., 2016)
This project is a model of interaction between Beacons (Bluetooth low energy) and mobile devices which are responsible for indicating, via voice, to blind or low vision users, the location of various points of interest, including: sanitary services, building names, identification of classrooms, ATMs, crosswalks, meeting areas in case of emergency, and identification of bus stops. The model is able to identify and prevent the user from hazards that may be encountered while traveling, such as construction zones, wet floor, stairs and escalators, among others.
Proyecto de Graduación (Maestría en Computación) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Computación, 2016.
Keywords: Talkback.; Toggle; Bluetooth; Tráfico de la aplicación; Moodboard; Personas con discapacidad; Discapacidad visual